Role of N-Glycosylation in FcγRIIIa interaction with IgG - Van Coillie, Julie; Schulz, Morten A.; Bentlage, Arthur E. H.; de Haan, Noortje; Ye, Zilu; Geerdes, Dionne M.; van Esch, Wim J. E.; Hafkenscheid, Lise; Miller, Rebecca L.; Narimatsu, Yoshiki; Vakhrushev, Sergey Y.; Yang, Zhang; et al. (Frontiers in Immunology, 2022)
Immunoglobulins G (IgG) and their Fc gamma receptors (FcγRs) play important roles in our immune system. The conserved N-glycan in the Fc region of IgG1 impacts interaction of IgG with FcγRs and the resulting effector functions, which has led to the design of antibody therapeutics with greatly improved antibody-dependent cell cytotoxicity (ADCC) activities. Studies have suggested that also N-glycosylation of the FcγRIII affects receptor interactions with IgG, but detailed studies of the interaction of IgG1 and FcγRIIIa with distinct N-glycans have been hindered by the natural heterogeneity in N-glycosylation. In this study, we employed comprehensive genetic engineering of the N-glycosylation capacities in mammalian cell lines to express IgG1 and FcγRIIIa with different N-glycan structures to more generally explore the role of N-glycosylation in IgG1:FcγRIIIa binding interactions. We included FcγRIIIa variants of both the 158F and 158V allotypes and investigated the key N-glycan features that affected binding affinity. Our study confirms that afucosylated IgG1 has the highest binding affinity to oligomannose FcγRIIIa, a glycan structure commonly found on Asn162 on FcγRIIIa expressed by NK cells but not monocytes or recombinantly expressed FcγRIIIa.